Application of Homeschooling in the Formation of Islamic Character an Indonesian Celebrity Children - Apit Fathurohman; Petrus Jacob Pattiasina; Ngumar Ngumar; Umar Sidiq (Al-Hayat: Journal of Islamic Education, 2022)
This research aims to reveal that some Indonesian artists believe homeschooling education is better than formal education, as is common in regular schools. Also, homeschooling is an alternative for not dropping out of school or education amid artists' busy schedules, especially Islamic education. This study uses a qualitative approach to the type of literature study. The primary data source is the document of the Regulation of the Minister of Education and Culture of the Republic of Indonesia Number 129 of 2014 concerning homeschooling. Secondary data is from journals, books, articles and other people's writings and statements about homeschooling. Data collection techniques used are documentation and observation. The triangulation technique does credibility. Data analysis was performed through data reduction, data presentation and conclusion. This research results that homeschooling education is in line with the Islamic perspective, namely honing children's talents as beings whose nature is accompanied by the nature of their respective talents and interests, and is appropriate among Indonesian celebrities in the formation of the Islamic character of children whose parents are more selective and on target in providing education with a harmonious example and habituation between children, tutors and parents.